An approach to sulfate geoengineering with surface emissions of carbonyl sulfide - I. Quaglia (Atmospheric Chemistry and Physics, 2022)
Sulfate geoengineering (SG) methods based on lower stratospheric tropical injection of sulfur dioxide (SO2) have been widely discussed in recent years, focusing on the direct and indirect effects they would have on the climate system. Here a potential alternative method is discussed, where sulfur emissions are located at the surface or in the troposphere in the form of carbonyl sulfide (COS) gas. There are two time-dependent chemistry–climate model experiments designed from the years 2021 to 2055, assuming a 40 Tg-S<mspace width="0.125em" linebreak="nobreak"/>yr-1<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="54pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="f2da400167d0543c1d92eef2d84cad3e"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-22-5757-2022-ie00001.svg" width="54pt" height="15pt" src="acp-22-5757-2022-ie00001.png"/></svg:svg> artificial global flux of COS, which is geographically distributed following the present-day anthropogenic COS surface emissions (SG-COS-SRF) or a 6 Tg-S<mspace width="0.125em" linebreak="nobreak"/>yr-1<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="54pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="163990e6943dee2fe272864c3ddbc533"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-22-5757-2022-ie00002.svg" width="54pt" height="15pt" src="acp-22-5757-2022-ie00002.png"/></svg:svg> injection of COS in the tropical upper troposphere (SG-COS-TTL). The budget of COS and sulfur species is discussed, as are the effects of both SG-COS strategies on the stratospheric sulfate aerosol optical depth (∼Δτ=0.080<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="66pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="1ed86419d1791fb3911b06402498c099"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-22-5757-2022-ie00003.svg" width="66pt" height="10pt" src="acp-22-5757-2022-ie00003.png"/></svg:svg> in the years 2046–2055), aerosol effective radius (0.46 µm), surface SOx deposition (+8.9 % for SG-COS-SRF; +3.3 % for SG-COS-TTL), and tropopause radiative forcing (RF; ∼-1.5<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="35pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="6c6a95f4e09a47dd93baf926c93fe4eb"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-22-5757-2022-ie00004.svg" width="35pt" height="10pt" src="acp-22-5757-2022-ie00004.png"/></svg:svg> W m−2 in all-sky conditions in both SG-COS experiments). Indirect effects on ozone, methane and stratospheric water vapour are also considered, along with the COS direct contribution. According to our model results, the resulting net RF is −1.3 W m−2, for SG-COS-SRF, and −1.5 W m−2, for SG-COS-TTL, and it is comparable to the corresponding RF of −1.7 W m−2 obtained with a sustained injection of 4 Tg-S<mspace width="0.125em" linebreak="nobreak"/>yr-1<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="54pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="3467dc9edfdf867b36605c0768e5e497"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-22-5757-2022-ie00005.svg" width="54pt" height="15pt" src="acp-22-5757-2022-ie00005.png"/></svg:svg> in the tropical lower stratosphere in the form of SO2 (SG-SO2, which is able to produce a comparable increase of the sulfate aerosol optical depth). Significant changes in the stratospheric ozone response are found in both SG-COS experiments with respect to SG-SO2 (∼5 DU versus +1.4 DU globally). According to the model results, the resulting ultraviolet B (UVB) perturbation at the surface accounts for −4.3 % as a global and annual average (versus −2.4 % in the SG-SO2 case), with a springtime Antarctic decrease of −2.7 % (versus a +5.8 % increase in the SG-SO2 experiment). Overall, we find that an increase in COS emissions may be feasible and produce a more latitudinally uniform forcing without the need for the deployment of stratospheric aircraft. However, our assumption that the rate of COS uptake by soils and plants does not vary with increasing COS concentrations will need to be investigated in future work, and more studies are needed on the prolonged exposure effects to higher COS values in humans and ecosystems.